2008
DOI: 10.1111/j.1601-0825.2008.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cytokeratin 17 protein in oral squamous cell carcinoma in vitro and in vivo

Abstract: Increased CK17 expression may play an important role in the carcinogenesis progression of OSCC; however, further studies on the molecular function of CK17 are encouraged to clear the precise mechanism of CK17 in OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 22 publications
4
42
0
1
Order By: Relevance
“…These results are consistent with the report of Wei et al 12) . This cytokeratin may also be used in the diagnosis of the presence or absence of epithelial dysplasia, or cancer.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results are consistent with the report of Wei et al 12) . This cytokeratin may also be used in the diagnosis of the presence or absence of epithelial dysplasia, or cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Epithelial dysplasia occurring on the tongue is most commonly presented and diagnosed as leukoplakia, and reports have indicated that several percents of leukoplakia undergo malignant changes 7,8) . Leukoplakia is a clinical diagnostic term, (2):123-130, 2010 reported [9][10][11][12][13] . However, the application of a combination of several immunohistochemical stains to diagnosis is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…2). After quantitative analysis, we confirmed about known markers, K 13, 17 and CD98 8,20,21 and validated whether this experiment reflected each lesion. In addition, we identifi ed K6hf as a candidate marker of OSCC (Table 1).…”
Section: Protein Identifi Cation By Lc/ms/msmentioning
confidence: 67%
“…W trakcie rozwoju nowotworu ekspresja keratyn jest utrzymywana, ale zmianie ulega wzór ich ekspresji, dlatego są one wykorzystywane jako markery zmian nowotworowych. W badaniach wykazano, że w obrę-bie guzów jamy ustnej zwiększonej ekspresji ulegają keratyny K8/K18, K17 i K14 (2,6,12,14,18,30,48,52), natomiast obniżoną aktywność wykazują K4, K5, K13 i K19 (2,6,18,19,25,30,36). W jednym z badań analizowano ekspresję KRT76 w błonie śluzowej policzków chomika.…”
Section: Markery Będące Wskaźnikami Procesu Kancerogenezyunclassified